1986
DOI: 10.1002/art.1780291007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an immunopathogenic basis for central nervous system disease in primary Sjögren's syndrome

Abstract: The pathogenesis of central nervous system complications in primary Sjögren's syndrome (CNS‐SS) is unknown. In order to determine whether patients with active CNS‐SS have cerebrospinal fluid (CSF) abnormalities indicative of CNS inflammation, CSF analyses from 30 patients with active CNS‐SS (SSA) were contrasted with those from 20 SS patients without CNS involvement (SSI) and 20 patients with systemic lupus erythematosus and active CNS disease (SLEA). Elevations of total protein concentration, IgG concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…The blood-brain barrier is generally intact in SS-related CNS involvement [13]. All patients showed evidence of intrathecal IgG synthesis demonstrated by raised CSF IgG index or CSF-specific oligoclonal bands, which is in accordance with previously published findings [13]. This observation may indicate a specific role of intrathecally synthesized IgG in SS-related CNS manifestations.…”
Section: Discussionsupporting
confidence: 80%
“…The blood-brain barrier is generally intact in SS-related CNS involvement [13]. All patients showed evidence of intrathecal IgG synthesis demonstrated by raised CSF IgG index or CSF-specific oligoclonal bands, which is in accordance with previously published findings [13]. This observation may indicate a specific role of intrathecally synthesized IgG in SS-related CNS manifestations.…”
Section: Discussionsupporting
confidence: 80%
“…However, data regarding CSF results in patients with Sjögren's syndrome are of a lesser volume. Indeed, one study included 30 patients with active CNS involvement [14] . However, CSF results are incomplete and the interpretation of OCBs (positive in 86% of 29 patients) underlies limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies reported routine CSF findings such as cell count, glucose, total protein level, and oligoclonal bands (OCBs) in case reports or small case series [4,[9][10][11][12][13] . In 1986, CSF cell count, total protein, and IgG profiles from 30 patients with CNS involvement due to Sjögren's syndrome were described [14] . Because CSF findings in patients with Sjögren's syndrome are still poorly defined, we performed a thorough evaluation of clinical and laboratory data with special emphasis on CSF.…”
Section: Cerebrospinal Fluid Findings Inmentioning
confidence: 99%
“…The neurological features seen in patients with primary SjS include seizure disorders [10], aseptic meningoencephalitis [12], symptoms mimicking multiple sclerosis [11], progressive dementia [6], and paraneoplastic-like syndrome [13].…”
Section: Discussionmentioning
confidence: 99%